Pendampingan Pembuatan Legalitas Usaha Dan Branding Produk UMKM Desa Ngampungan - Nurul Aulia Dewi; Rahman Amrullah Suwaidi (Fakultas Teknik Universitas Cenderawasih, 2023)
Product branding is a form of marketing strategy and the identity of a product that can differentiate it from other products. Branding aims to attract consumers with the value offered. Apart from branding, business legality, one of which is NIB also provides a sense of security for consumers to buy products. Most of the business actors in Ngampungan Village do not have a brand and NIB, such as MSMEs Banana Chips owned by Mrs. Khusnul and Jamu owned by Mrs. Jumaidah. Seeing this problem, a solution is provided by assisting in making business legality, making brands, logos and product labels. The method used is interviews with business actors and then analyzes the existing problems. The purpose of these activities is to increase market competitiveness and also expand market share. The output produced by the author provides logo designs and business labels, assists in making Instagram social media, and helps make NIB.